Structured Ni@NaA zeolite supported on silicon carbide foam catalysts for catalytic carbon dioxide methanation. Issue 11 (18th August 2020) - Zhang, Rongxin; Chen, Huanhao; Mu, Yibing; Chansai, Sarayute; Ou, Xiaoxia; Hardacre, Christopher; Jiao, Yilai; Fan, Xiaolei
Abstract: Carbon dioxide (CO2 ) conversion is an important yet challenging topic, which helps to address climate change challenge. Catalytic CO2 methanation is one of the methods to convert CO2, however, it is limited by kinetics. This work developed a structured Ni@NaA zeolite supported on silicon carbide (SiC) foam catalyst (i.e., Ni@NaA‐SiC), which demonstrated an excellent performance with a CO2 conversion of 82%, being comparable to the corresponding equilibrium conversion, and CH4 selectivity of 95% at 400°C. The activation energy for CO2 conversion over the 15Ni@NaA‐SiC catalyst is about 31 kJ mol −1, being significantly lower than that of the 15Ni@NaA pelletized catalyst (i.e., 84 kJ mol −1 ). Additionally, the structured catalyst was highly stable with sustained CO2 conversion at 78.7 ± 1.4% and selectivity to CH4 at 97.7 ± 0.2% over an 80 hr longevity test. In situ diffuse reflectance infrared Fourier transform spectroscopy‐mass spectroscopy characterization revealed that catalysis over the structured catalyst proceeded primarily via the CO free mechanism.